2020
DOI: 10.1155/2020/8732308
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model for pH Variation Resulted from Interaction of Aqueous Solution Contaminated with Nickel Ions and Cement Kiln Dust

Abstract: Reaction term in the transport equation which described the migration of metal ions in the porous medium is frequently represented by conventional kinetic models such as pseudo-first order, pseudo-second order, and others. Unfortunately, these models are applicable for the constant value of solution pH, and they cannot simulate the real situation in the field scale where this pH may be changed with time. Accordingly, the present study is a good attempt to derive the kinetic model that can simulate the change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results of the FT-IR analysis for wavenumbers ranging from 400 to 4000 cm -1 (Figure 2(b)) was used to identify the working functional groups for PKD, coated iron slag, coated iron slag loaded with Pb +2 and Cd +2 ions, and virgin iron slag. According to the spectra, the OH group is represented by a broad and strong peak at wavenumber 3442.3 cm -1 [24]. The C-C group vibration can be linked to peak values of 554.4,675.93, 704.9, 811.8, and 894.7 cm -1 that were found.…”
Section: Figure 2 X-ray Diffraction (Xrd) Analysis; Ft-ir Analysismentioning
confidence: 95%
“…The results of the FT-IR analysis for wavenumbers ranging from 400 to 4000 cm -1 (Figure 2(b)) was used to identify the working functional groups for PKD, coated iron slag, coated iron slag loaded with Pb +2 and Cd +2 ions, and virgin iron slag. According to the spectra, the OH group is represented by a broad and strong peak at wavenumber 3442.3 cm -1 [24]. The C-C group vibration can be linked to peak values of 554.4,675.93, 704.9, 811.8, and 894.7 cm -1 that were found.…”
Section: Figure 2 X-ray Diffraction (Xrd) Analysis; Ft-ir Analysismentioning
confidence: 95%
“…Figure 4 elucidates the FT-IR spectra for interaction of WFS with Pb +2 and Ni +2 ; however, this figure in combination with Table 3 Generally, two mechanisms for adsorption of heavy metals can be recognized; (i) specific adsorption, which is characterized by more selective and less reversible reactions including chemisorbed inner-sphere complexes, and (ii) nonspecific adsorption (or ion exchange), which involves rather weak and less selective outer-sphere complexes. Journal of Chemistry Specific adsorption occurs slowly and brings about strong and irreversible binding of heavy metal ions with adsorbent [49]. Meanwhile, cation exchange is a form of outer-sphere complexation with only weak covalent bonding between metals and charged adsorbent surfaces.…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 99%
“…The results indicated that the most effective conguration to safeguard a particular location is to surround it on three sides opposing the ow direction compared to a continuous barrier. 22 The use of commercial sorbents, 9,[23][24][25][26] industrial wastes resulted as byproducts from various industries, [27][28][29] or manufacturing new valuable sorbents from these wastes [30][31][32] for elimination of chemicals from contaminated water is a crucial eld that has studied recently. This study aims to utilize clay, an abundant and cost-effective material in the Iraqi environment, as an LPB to control the migration of lead and nickel ions through groundwater and protect water resources.…”
Section: Introductionmentioning
confidence: 99%